Implementation of a Web-Based Production-Cycle Accounting Information System for the Culinary MSME RM Pawon Selaras, Minahasa Regency - Pricilia Joice Pesak; Lenny Leorina Evinita; Florence Olivia Moroki; Jaqueline E. M Tangkau; Miryam Pingkan Lonto (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to assist RM Pawon Selaras, a culinary micro, small, and medium-sized enterprise (MSME) located in Perum Unima, Minahasa Regency, in digitalizing its production management through a web-based Accounting Information System (AIS). The program adopted a participatory mentoring approach implemented from April to June 2026 through six stages: planning, needs analysis, system design, implementation, testing using Black Box Testing, and system deployment with maintenance. Program evaluation was conducted qualitatively through semi-structured interviews, observations, and documentation to assess system usability and partner capacity development. The resulting web-based application provides integrated features for raw material management, menu and recipe management, production planning, quality control, waste recording, inventory updating, and the generation of production and cost of goods manufactured reports. The program produced two major outcomes: the successful implementation of a functional digital information system and enhanced partner capacity in managing production records and operational information. The partner transitioned from intuitive, memory-based practices to structured, integrated, and data-driven documentation that supports pricing decisions and business performance evaluation. These findings suggest that the digital transformation of MSMEs can begin by addressing internal operational and record-management needs rather than focusing solely on digital marketing, and that sustained mentoring plays a critical role in facilitating technology adoption. Further evaluation using quantitative performance indicators is recommended to assess improvements in operational efficiency and waste reduction.